Análise da influência do conhecimento sobre diabetes e perfil de metilação dos microRNAs -9-1, -9-3 e 137 sobre parâmetros bioquímicos, inflamatórios, estresse oxidativo e antropométricos em população diabética - Assis, Caroline Severo de (2019)
Introduction: Type 2 Diabetes Mellitus is a chronic disease of high global prevalence. Because it is multifactorial, several aggravating conditions can be controlled from prevention strategies that go through health education and patient awareness to self care. Overweight and obesity are factors that in addition to Diabetes can influence the appearance of complications such as retinopathy and diabetic nephropathy. Genetic and epigenetic aspects may influence the development of diabetes, and some microRNAs have already been identified as risk factors. Objective: To analyze the impact of the relationship between the patient's knowledge about diabetes, biochemical, inflammatory, oxidative stress and anthropometric parameters and the effect of the promoter methylation profile of the genes coding for miRs-9-1, 9-3 and 137. Methodology: This is a cross-sectional study from a larger study carried out at the Lauro Wanderley University Hospital, located in the city of João Pessoa / Paraíba, with individuals using the nephrology and ophthalmology services of the hospital, who used the information anthropometric and Diabetes Knowledge Scale Questionnaire, already collected from the participants who composed the sample. A total of 103 patients with DM2, older than 40 years, with diagnosis time between 5 and 10 years were included. The methylation analyzes were performed on DNA samples transformed by the sodium bisulfite technique, and analyzed by the Polymerase Chain Reaction technique specific for methylation. The methylation profiles of the microRNAs were performed with aliquots of previously isolated leukocyte DNA. Determinations of glucose, creatinine, total cholesterol, triglycerides, glycated hemoglobin, C-reactive protein, α1-acid glycoprotein, HDL cholesterol were determined by commercial kits and calculated LDL cholesterol. Malondialdehyde, total antioxidant capacity were determined by chemical methods. Results: it was found that the group with higher knowledge was younger (p= 0.0070) and arterial hypertension was a significant variable in the low knowledge group (p= 0.0061). When separated by the presence of diabetic complications, the high knowledge and methylated profile of miR-9-1 were shown to be associated with diabetic retinopathy and nephropathy (p= 0.0051). Excess weight (p= 0.0108) and obesity (p= 0.0019) were associated with low knowledge and a methylated profile for miR-137. Conclusion: The results of the study suggest that the presence of complications of diabetes and aggravating clinical conditions are related to the methylated profiles of miR-137 in low knowledge and miR-9-1 methylated in patients with high knowledge. These data, together with additional studies, should contribute to the use of miRs-137 and 9-1 as epigenetic biomarkers together with the knowledge of the individual in the prediction of diabetic complications and aggravating clinical conditions.